Detection of human GPCR activity in drosophila S2 cells using the Tango system - Salim, Emil; Hori, Aki; Matsubara, Kohei; Takano-Shimizu, Toshiyuki; Pratomo, Andre Rizky; Marianne, Marianne; Syahputra, Armia; Husori, Dadang Irfan; Inoue, Asuka; Abdullah, Maryam Aisyah; Shamsudin, Nur Farisya; Rullah, Kamal; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
G protein-coupled receptors (GPCRs) are essential cell surface proteins involved in transducing extracellular signals into intracellular responses, regulating various physiological processes. This study validated the use of the Tango assay, a sensitive method for detecting GPCR activation, in Drosophila Schneider 2 (S2) cells, focusing on the human Dopamine Receptor D4 (DRD4). Plasmids encoding the LexA-tagged human DRD4 receptor and a luciferase reporter were co-transfected into Drosophila S2 cells and stimulated with dopamine. Receptor activation was measured by quantifying the luciferase activity. The system showed high specificity for dopamine, with no activation in response to octopamine, a non-ligand for DRD4. Furthermore, the system effectively detects activation by a novel compound. These results demonstrate that Drosophila S2 cells, coupled with the Tango assay, provide a viable model for studying human GPCR function and ligand specificity. This system enables the rapid screening of potential GPCR ligands in a cost-effective cellular model.